British Society of Gastroenterology Endoscopy Quality Improvement Programme (BSG EQIP): Implementing new endoscopic techniques and technologies into clinical practice - Bhandari, Pradeep (Frontline Gastroenterol, 2019)
Endoscopy has rapidly evolved from a diagnostic modality to a therapeutic tool with the advent of new technologies (medical devices or imaging) and techniques (types of procedures). Although the rapid advancement of technology is welcomed, this can pose its own problems if there is no robust system in place to assess the safety and efficacy of new endoscopic devices or practices or guide its use among clinicians prior to adoption. This is unlike the rigorous process that medical drugs need to go through from preclinical to clinical phases of development, often with controlled trials being conducted prior to integration of a new drug into clinical practice. In this review, we will identify the problems related to implementation of new technologies and techniques as well as propose solutions. We will outline the use of comparative effectiveness studies as a model for assessing new technologies and provide a structured pathway to support clinicians in their endeavour to introduce new devices or procedures in their clinical practice safely. We will also discuss the role of the British Society of Gastroenterology in risk stratifying new techniques and supporting clinicians in setting up national registries, training and business case development. This review will provide a framework for improving the quality and safety of our current practice of implementing new endoscopic technologies and techniques in the National Health Service.